Development of Kalman Filter based Algorithms for Fringe Pattern Analysis - Sharma, Shikha (My University, 2024)
The purpose of fringe pattern analysis is to retrieve the phase from the fringe pattern. The phase retrieval is essential from the fringe pattern in order to derive the object information. Therefore, demand for the phase information has promoted the development of fringe analysis techniques. Spatial fringe analysis techniques typically involve different operations such as fringe denoising, fringe normalization, and fringe pattern demodulation for the phase estimation. In some cases, phase aberration compensation is also required to be performed. The thesis presents a number of spatial fringe processing algorithms based on the application of Kalman filter.
Kulkarni, Vinayak
Keywords: Fringe Analysis; Fringe Denoising; Fringe Pattern Normalization; Fringe Pattern Demodulation; Phase Estimation; Speckle Noise; Kalman Filter; Extended Kalman Filter